Development of an integrated entrepreneurship model based on the principles of circular and sharing economy: theoretical substitution and practical analysis - Pererva, P. G.; Kobielieva, Tetiana; Keršys, Robertas; Moroz, Karyna; Kniaz, Viktor; Kosenko, Oleksandra; Tkachova, Nadiia; Nagy, Szabolcs; Kosenko, Andriy; Tkachov, M. M. (Технологічний центр, 2026)
The object ofresearch is the process offormation and development ofmodern entrepreneurship in the context ofthe transition from a linear model to a circular and sharing economy, which are currently focused on the principles ofsustainable development. The paper analyzes the current state and prospects for the development ofentrepreneurship, which operates on the principles ofclosed production cycles, extending the life cycle ofproducts and reusing raw materials and materials. An integrated model ofentrepreneurship based on the principles ofa circular and sharing economy is proposed. The theoretical and practical essence ofthese economic models is considered, the principles oftheir construction are further developed, and signifiant diffrences from the traditional provisions ofa linear economy are formed. It is substantiated that the gradual transition from a linear economic model ofmanagement to circular and sharing models ofthe economy is dictated by the presence ofenvironmental challenges, as well as the limitation ofnatural resources. Trends in the fild ofsharing business, which are based on the joint use ofresources by the asset owner and other consumers, are studied. The global experience ofimplementing these approaches has been analyzed and summarized, and the prospects for their development have been considered. It has been determined that over the past 10 years, the use ofthe circular economy concept in the world has increased 15 times ( from 0.8% to 12% ofenterprises), and the concept ofthe sharing economy has increased 10 times ( from 0.2% to 2%). The research results confim the integration oftheoretical and practical provisions ofthe circular and sharing economy into global business models. This contributes to increasing the effiency ofresource use, increases the level ofcompetitiveness ofenterprises, and creates stable social and environmental benefis. Practical recommendations for Ukrainian entrepreneurs are proposed, the use ofwhich will help adapt modern business to global trends in resource conservation within the framework ofEuropean integration and post-war economic recovery.
Keywords: entrepreneurship; circular and sharing business; sustainable development; integrated business model; information potential; renewable energy